Aplikasi Handphone Pengingat Waktu Sholat Menggunakan Java 2 Micro Edition - Tito Pinandita (JUITA : Jurnal Informatika, 2010)
Praying five times a day is an obligation of worship for Muslims in the world. Praying five times a timetable that has been determined according to the teachings of the Prophet Muhammad, praying five times where the schedule varies according to position on the earth's surface area. J2ME software capabilities that support the creation of applications on mobile phones inspiration to make the application prayer time schedule stored in the mobile phone making it easier for users to be able to know the timeline of prayer according to the selected city name. Prayer time schedules are included in the mobile applies to 86 major cities in Indonesia. Testing the application using the NetBeans IDE emulator, emulator Nokia S40 6th edition and apply it on a mobile phone that supports Java applications micro. Application timetable for prayers that are stored in the phone can be used anywhere in the area although there is no network signal carrier